Evaluation of six geothermal heat flux maps for the Antarctic Lambert:Amery glacial system - Kang, Haraong; Zhao, Liyun; Wolovick, Michael; Moore, John C. (The Cryosphere, 2022)
Basal thermal conditions play an important role in ice sheet dynamics, and they are sensitive to geothermal heat flux (GHF). Here we estimate the basal thermal conditions, including basal temperature, basal melt rate, and friction heat underneath the Lambert–Amery Glacier system in eastern Antarctica, using a combination of a forward model and an inversion from a 3D ice flow model. We assess the sensitivity and uncertainty of basal thermal conditions using six different GHF maps. We evaluate the modelled results using all observed subglacial lakes. The different GHF maps lead to large differences in simulated spatial patterns of temperate basal conditions. The two recent GHF fields inverted from aerial geomagnetic observations have the highest GHF, produce the largest warm-based area, and match the observed distribution of subglacial lakes better than the other GHFs. The modelled basal melt rate reaches 10 to hundreds of millimetres per year locally in the Lambert, Lepekhin, and Kronshtadtskiy glaciers feeding the Amery Ice Shelf and ranges from 0–5 mm yr−1 on the temperate base of the vast inland region.